Public interest and private rights in social media - Reiman, Cornelis; ScienceDirect eBooks (Oxford : Chandos Publishing, 2012)
Social media has an increasing role in the public and private world. This raises socio-political and legal issues in the corporate and academic spheres. Public Interest and Private Rights in Social Media provides insight into the use, impact and future of social media. The contributors provide guidance on social media and society, particularly the use of social media in the corporate sector and academia, the rising influence of social media in public and political opinion making, and the legal implications of social media. The Editor brings together unusual perspectives on the use of social media, both in developed and developing countries. This title consists of twelve chapters, each covering a salient topic, including: social media in the context of global media; the First Amendment and online calls for action; social media and the rule of law; social networks and the self; social media strategy in the public sector; social media in humanitarian work; social media as a tool in business education; social media and the 'continuum of transparency'; business and social media; making a difference to customer service with social media; social analytics data and platforms; and altruism as a valuable dimension of the digital age. Provides a guide to the key components of corporate and academic use of social mediaOffers technological and non-technological, legal, and international perspectivesConsiders socio-political impact and legal issues.
Social media growth and global change / Cornelis Reiman -- Flash rob or protest movement: the First Amendment and regulating online calls to action / Margot Kaminski -- World justice: the rule of law around the world / Kurt Ramin and Antje Meyer -- Default metaphysics: social networks and the self / Florian Hadler and Gabriel Yoran -- A service-oriented approach to public sector social media strategy / Marshall Sitten -- Social media in the humanities space / Claudia Gonzalez and Alan Rosenblatt -- Social media: the new tool in business education / Susan Bandias and Anthony Gliding -- Social media: does it generate the continuum of transparency in organisations? / Andrew Creed and Ambika Zutshi -- Social media: blessing or curse? -- A business perspective / Richard Messik -- Improving the customer experience: how social media can make a difference / Urs E. Gattiker -- The uses and accuracy of social analytics data and platforms / Marshall Sponder -- Altruism: a valuable dimension of the digital age / Russell Yardley.
Includes bibliographical references and index.
Print version record.
Elsevier
Safari Books Online
Keywords: Social media; Online social networks; PSYCHOLOGY -- Social Psychology; Online social networks; Social media; Electronic books